2020
DOI: 10.1051/swsc/2020034
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Space Weather Modeling Framework (SWMF) for applications in northern Europe

Abstract: In this study we investigate the performance of the University of Michigan’s Space Weather Modeling Framework (SWMF) in prediction of ground magnetic perturbations (∆B) and their rate of change with time (dB/dt), which is directly connected to geomagnetically induced currents (GICs). We use the SWMF set-up where the global magnetosphere provided by the Block Adaptive Tree Solar-wind Roe-type Upwind Scheme (BATS-R-US) MHD code, is coupled to the inner magnetosphere and the ionospheric electrodynamics. The valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Kwagala et al. (2020) reported that the northward ground Δ B from SWMF was better predicted at sub‐auroral latitudes (58°–67°) which generally agrees with our observations. In our study, one reason for this is that NUR did not measure the large B X depressions that dominated at higher latitudes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Kwagala et al. (2020) reported that the northward ground Δ B from SWMF was better predicted at sub‐auroral latitudes (58°–67°) which generally agrees with our observations. In our study, one reason for this is that NUR did not measure the large B X depressions that dominated at higher latitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Many relevant previous studies have compared magnetometer measurements with simulated ground magnetic fields (Kwagala et al, 2020;Pulkkinen et al, 2010Pulkkinen et al, , 2011Pulkkinen et al, , 2013Shao et al, 2002;Yu & Ridley, 2008) using a variety of global MHD models. Shao et al (2002) utilized the Lyon-Fedder-Mobarry (LFM) which showed reasonable agreement but tended to underestimate the observations during active periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MHDbased magnetic field captures less of the short-period variability. These results are consistent with results of Kwagala et al (2020), who carried out SWMF simulations for a number of space weather events and compared SWMF-based (external) magnetic fields with observed ones at a number of locations in northern Europe. According to their modeling results, the SWMF predicts the northward component of external magnetic field perturbations better than the eastward component in auroral and subauroral regions, which is also the case in our modeling of the total magnetic field.…”
Section: Comparing Results At a Number Of Locations In The Regionsupporting
confidence: 89%
“…According to their modeling results, the SWMF predicts the northward component of external magnetic field perturbations better than the eastward component in auroral and subauroral regions, which is also the case in our modeling of the total magnetic field. As it was mentioned by Kwagala et al (2020), poor prediction of the eastward component of magnetic field perturbations is directly related to the northward current density in the ionosphere and may arise from the misplacement of the currents in the SWMF with respect to the magnetometer stations. Similar to the MHD-based magnetic field, the MHD-based GEF is underestimated compared to the SECSbased GEF.…”
Section: Comparing Results At a Number Of Locations In The Regionmentioning
confidence: 95%